Tracing Seal Predation Back to the Source Colony of Their Penguin Prey: A Trace Element and Stable Isotope Analysis - Reinhold, Sarah-Lena; Goldsworthy, Simon D.; Arnould, John P.Y.; Gillanders, Bronwyn M.; Connell, Sean D.; McIntosh, Rebecca R. (Frontiers in Marine Science, 2022)
Marine predators recovering from historic, commercial, over-harvesting can create conservation challenges when they prey on vulnerable species. Pinniped predation of seabirds presents one such challenge and identifying the source colonies experiencing seal predation are needed to inform conservation management and decision planning. Here, we present a novel application of stable isotope and trace element techniques to identify the source colony of little penguins (Eudyptula minor) predated by long-nosed fur seals (Arctocephalus forsteri). We created baseline biochemical ‘feather-prints’ from feathers for six major breeding colonies across south-east Australia to compare with feathers from predated penguins recovered from seal scats. Feeding trials of captive seals confirmed that digestion of penguin feathers did not compromise stable isotope (δ13C and δ15N) or trace element (Al, Ti, Sr and Mg) signatures. The resulting biochemical ‘feather-prints’ were found to be robust in being correctly classified to local sites (78%) and broader regions (85%). The distinguishing ‘feather-prints’ appeared to be driven by industrial inputs from land, colony-specific foraging patterns and potentially proximity to oceanographic systems (i.e. upwelling). Here, we show that 46-70% of predated feathers were assigned to ‘local’ penguin colonies. We consider that the regional penguin abundances and the proximity of their colonies to seal sites, as well as demographic-specific foraging patterns may shape their contribution to seal diet at local, regional and inter-regional scales. This diagnostic tool is powerful, having broad applications identifying seabird colonies at greatest risk to pinniped predation and informing targeted, site-specific, conservation effort.